Elogio del teoricismo: práctica teórica e inconsciente filosófico en la problemática althusseriana - Romé, Natalia (2015)
This article explores two thesis. The first one proposes to revise the purported “theoricism” of Louis Althusser in order to highlight that his developments on the problem of knowledge and the connection between science and philosophy are not only a necessary step in persuit of marxist theory and its criticism of idealist epistemology, but an indispensable condition for political thought itself. The second thesis considers the consequences of the proccesual and strategic althusserian thought for the materialist philosophy, articulated around the category of overdetermination, as symptomatic reading of a topic and a position taken in a controversial field.